2016
DOI: 10.3389/fpls.2016.00652
|View full text |Cite
|
Sign up to set email alerts
|

Tissue- and Cell-Specific Cytokinin Activity in Populus × canescens Monitored by ARR5::GUS Reporter Lines in Summer and Winter

Abstract: Cytokinins play an important role in vascular development. But knowledge on the cellular localization of this growth hormone in the stem and other organs of woody plants is lacking. The main focus of this study was to investigate the occurrence and cellular localization of active cytokinins in leaves, roots, and along the stem of Populus × canescens and to find out how the pattern is changed between summer and winter. An ARR5::GUS reporter construct was used to monitor distribution of active cytokinins in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 63 publications
5
15
0
Order By: Relevance
“…However, the detection of the nucleotide fraction of iP, iPRP, within the cell pellet, as well as the other FB, R, and 2MeS CK forms suggests that the complexity of mammalian CK production and metabolism is greater than previously understood. Furthermore, in the recent report on CK profiles in canine tissues, a tissue‐ and organ‐specific trend was observed, which to some extent resembles the organ‐specific CK dynamics in plants . Coupling these new findings about mammalian CKs, we suggest there is a greater role for the breakdown product of iPR‐tRNA turnover as is evidenced by the numerous CK forms detected both intracellularly and extracellularly.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the detection of the nucleotide fraction of iP, iPRP, within the cell pellet, as well as the other FB, R, and 2MeS CK forms suggests that the complexity of mammalian CK production and metabolism is greater than previously understood. Furthermore, in the recent report on CK profiles in canine tissues, a tissue‐ and organ‐specific trend was observed, which to some extent resembles the organ‐specific CK dynamics in plants . Coupling these new findings about mammalian CKs, we suggest there is a greater role for the breakdown product of iPR‐tRNA turnover as is evidenced by the numerous CK forms detected both intracellularly and extracellularly.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, in the recent report on CK profiles in canine tissues, a tissue-and organ-specific trend was observed, which to some extent resembles the organ-specific CK dynamics in plants. 32,46,47 Coupling these new findings about mammalian CKs, we suggest there is a greater role for the breakdown product of iPR-tRNA turnover as is evidenced by the numerous CK forms detected both intracellularly and extracellularly.…”
Section: Hela Ck Metabolismsupporting
confidence: 58%
“…In poplar, overexpression of the Arabidopsis CYTOKININ OXIDASE 2, an enzyme involved in cytokinin catabolism, resulted in non-detectable levels of the cytokinin trans-zeatin and its storage form zeatin-O-glucoside and lead to a reduced number of cambial cells, resulting in impaired wood formation [87]. Moreover, cytokinin activity was high in primary meristems supporting its function in early wood formation processes [88] and reduced in the cambial zone of drought stressed poplar, indicating a regulatory function of cytokinins under drought stress [89]. There is now increasing evidence that cytokinins interact with jasmonic acid.…”
Section: Phytohormones Mediate Xylem Changes Under Droughtmentioning
confidence: 99%
“…In this pathway, type-A ARRs ( Arabidopsis response regulators) are the primary response genes for cytokinins in Arabidopsis ( D’Agostino et al 2000 ). Expression of an Arabidopsis ARR5::GUS reporter construct in poplar indicated conserved functions of the response regulator in both species ( Paul et al 2016 ). A total of 10 type-A RR genes are present in Arabidopsis ( D’Agostino et al 2000 ; Schaller et al 2008 ; Pils and Heyl 2009 ) and 11 were reported in Populus trichocarpa ( Ramírez-Carvajal et al 2008 ; Immanen et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%